New Media in Global Politics: the Role of Media in the Image Construction of African Region - Phoebe Inggrid Angeline Romauli; Nathanael Jusac Lie; Rizqa Aliefiarahma; Aurelia Syafina Luthfi; Glen Matthew; Said Rivaldi Assagaf (Yayasan Ilomata, 2023)
New media is one of the rapid development of technology that makes the exchange of information happen more quickly. Communication patterns in this information technology era are convergent. This is due to the current technological capabilities that enable existing information to be disseminated widely and swiftly. The convergence characteristics of this information technology era lead to the transformation of conventional media into new digital forms. The massive amount of information that can be disseminated through the media makes it one of the big power holders to shape an image. The greater the influence in new media, the greater the tendency for the information to be known and understood. The dissemination of information using digital media is practiced by the African Region to construct its own image for the purpose of changing the international public's view of the region. In this study, a qualitative method with a case study approach is implemented. The research findings revealed that the African Region has utilized digital diplomacy, public diplomacy and the concept of multi-track diplomacy to improve its image. However, there is a need for a better coordination from governments in African countries to develop a positive image.